Een dakloos gedenkteken voor Michiel de Ruyter - Doedens, Jaap (Acta Neerlandica, 2026)
Almost unbeknownst to virtually anyone, the fragments of a monument commemorating the liberation of galley slaves by Michiel de Ruyter lay for years in the parking garage of the Reformed Theological Seminary in Pápa. Originally, this memorial stood in the courtyard of the military academy, the Zrínyi Miklós Nemzetvédelmi Egyetem (Miklós Zrínyi Defense University) on Üllői Street in Budapest. It was erected in 2002 to commemorate the liberation of the Hungarian ministers who had been sentenced to the galleys and were freed by Michiel de Ruyter in Naples in 1676. The monument was designed and created by Colonel Dr. Lajos Berek, who was also the rector of that university. When this military academy moved to the campus on the Hungária ring road in 2008, the old building was sold. The monument was taken down. The Bolyai János Honvéd Alapítvány (János Bolyai Defense Foundation) donated the memorial to the Protestáns Tábori Püspökség (Protestant Military Diocese). The new owner would look for a new location for the statue. Since there was no place to put it up again at that time, they looked for a place where it could be stored “temporarily.” That place was the parking garage of the Reformed Theological Seminary in Pápa.